The Total Incidence of Complications and the Impact of an Anticoagulation Regime on Adverse Events After Cryoballoon Ablation of Atrial Fibrillation: A Single‐Center Study of 409 Patients. Issue 3 (June 2016) - Koektuerk, Buelent; Turan, Cem H.; Yorgun, Hikmet; Keskin, Kerim; Schoett, Moritz; Dahmen, Alina; Gorr, Eduard; Yang, Alexander; Hoppe, Christian; Horlitz, Marc; Turan, Ramazan G.
Summary: Aim: Data evaluating the complications of pulmonary vein isolation (PVI) using second‐generation cryoballoons (CB) related to different anticoagulation regimes are limited. This study evaluates the total complications and the impact of novel oral anticoagulants (NOACs) compared to phenprocoumon on adverse events in the setting of PVI using CB. Methods and results: PVI was performed using second‐generation CB by two experienced investigators. A total of 409 patients (58.9% male; mean age = 61 ± 10 years) with atrial fibrillation were included in this study. In group I, 150/409 (36.7%) patients received phenprocoumon therapy, and in group II, 259/409 (63.3%) patients were treated with NOACs (rivaroxaban: n = 193; dabigatran: n = 48; and apixaban: n = 18). In both groups, the rates of major complications were similar (group I [phenprocoumon]: four pts (2.7%) vs. Group II [NOACs]: seven pts (2.7%); P  = 0.999). In this cohort, 275 patients were ablated with the bonus freeze protocol, and 134 patients were ablated without bonus freezes. The procedure duration significantly decreased with the bonus freeze protocol from 102.3 ± 24.6 min to 68.5 ± 16.2 min ( P < 0.001). The impact of the bonus freeze on the postprocedural increase of C‐reactive protein (CRP) levels was significant compared to the postprocedural CRP levels after procedures without the bonus freeze protocol (postprocedural CRP level+ bonus protocol: 1.6 ± 1.2 mg/L vs. postprocedural CRP level+ nonbonus protocol: 1.3 ± 1.3 mg/L; P  = 0.04). Conclusion: The incidence of adverse events in PVI using the second‐generation CB with the periprocedural administration of NAOCs was not significantly different compared to phenprocoumon. Further, large‐scale randomized studies are needed to evaluate the safety of two anticoagulation regimes comparing vitamin K antagonists and NOACs, as well as different NOAC regimes, in patients undergoing PVI using cryoballoon ablation.